2018
DOI: 10.14254/2071-8330.2018/11-2/8
|View full text |Cite
|
Sign up to set email alerts
|

Foreign aid, human capital and economic growth nexus: Evidence from Nigeria

Abstract: This study investigates the link between aid and human capital in promoting economic growth of Nigeria. The study used two models; the first model was used to test the validity of the medicine model in Nigeria; while the extended model was used to investigate the effect of aid and human capital shocks on growth using Engle-Granger and Vector Error Correction Model (VECM) estimation techniques respectively. The findings from the first model suggest that persistent increase in foreign aid flows beyond a particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 43 publications
5
51
0
Order By: Relevance
“…Note that the 0.09 percent increase in economic growth is as a result of a 1 percent increase in gross fixed capital formation. This reveals that gross fixed capital formation impacts economic growth positively (Fashina et al, 2018;Sethi; Note: * , * * , and * * * indicate statistical significance at the 1 percent, 5 percent, and 10 percent levels, respectively. SOURCE: Authors compilation.…”
Section: <1985>mentioning
confidence: 91%
See 2 more Smart Citations
“…Note that the 0.09 percent increase in economic growth is as a result of a 1 percent increase in gross fixed capital formation. This reveals that gross fixed capital formation impacts economic growth positively (Fashina et al, 2018;Sethi; Note: * , * * , and * * * indicate statistical significance at the 1 percent, 5 percent, and 10 percent levels, respectively. SOURCE: Authors compilation.…”
Section: <1985>mentioning
confidence: 91%
“…The opposite is true of most African economies because they remained backward given the constant flow of foreign 1 Daud (2012) , Trinh Tra (2014), Mohapatra et al (2016), Gomanee et al (2003), and Clist (2016) found aid-growth interaction to be positive. Cuberes and Tsui (2011), Kabete (2008), Ahmed (2014), Hotouom (2015), Kawthar and Mohamed (2017), and found a negative aid-growth relationship, and Fashina et al (2018), Dhakal et al (1996), Kolawole, (2013), Ramadhan et al (2016), and Tekin (2012) found no significant aid-growth relationship.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Among other studies offering econometric models for the variables in question, one can also mention Dougherty, (1992), Goldberger (1990), Greene (1993), Pindyck and Rubinfeld (1991), Simionescu et al (2016), Korauš et al (2017), Kasperowicz (2014), Kaigorodova et al (2018), Fashina et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of ensuring economic security of the country is one of the key aspects in the macroeconomic policy of developed and developing countries of the world (Bednar and Halaskova, 2018;Bhowmik, 2018;Fashina et al, 2018;Lyeonov et al, 2018;Milovic and Jocovic, 2017;Nguedie, 2018;Soylu et al, 2018;Vasylieva et al, 2018). The economic security of the state characterizes the condition of the national economy, which protects national interests, resistance to internal and external threats, the ability to develop and protect the vital interests of people, society, and the state.…”
Section: Introductionmentioning
confidence: 99%